Influence of soil pH and organic matter on germination and seedling growth attributes of Ailanthus excelsa Roxb. - Masilamani, P. (Indian Journal of Agroforestry, 2020)
An experiment was conducted to find out influence of different soil pH and organic matter on germination, seedling growth and chemical attributes of Ailanthus excelsa. The seeds were sown in soil with different pH (8.1, 9.0, 10.2 and 10.5), different pH soil mixed with sand + farmyard manure (2:1:1 ratio) and control (red earth + sand + farmyard manure at 2:1:1 ratio). Significant differences were observed among different treatment for all the parameters of germination and seedling growth attributes of 21 days old seedlings; and survival percentage, seedling growth attributes and chemical constituents of 180 days old seedlings. This species is able to tolerate extreme soil pH of 10.5, when the soil is mixed with sand and farm yard manure at 2:1:1 ratio, in terms of germination, seedling growth and chemical attributes of the seedlings.